Current approach in recurrent pregnancy loss - Pacheco, José (2009)
Recurrent pregnancy loss study approach has been related to progress in genetics and molecular biology as well as better diagnosis methods. In this review we recall current knowledge on the etiology, diagnosis and treatment of recurrent pregnancy loss, as well as its repercussion in the couple with subfertility due to this cause.